Discrete-Modulated Coherent-State Quantum Key Distribution with Basis-Encoding - Mingxuan Guo; Peng Huang; Le Huang; Xiaojuan Liao; Xueqin Jiang; Tao Wang; Guihua Zeng (Research)
Discrete-modulated coherent-state continuous-variable quantum key distribution (DMCS-CVQKD) is of great value for its simple implementation. However, the traditional DMCS-CVQKD scheme cannot tolerate the high channel excess noise and channel loss, compared to the Gaussian-modulated scheme, and its error correction is still difficult. In this paper, we propose a discrete-modulated coherent-state basis-encoding quantum key distribution (DMCS-BE-QKD) protocol, where the secret keys are encoded in the random choice of 2 measurement bases, i.e., the conjugate quadratures X and P of discrete-modulated coherent states, and it only needs simple binary sequence error correction. We analyze the secret key rate of DMCS-BE-QKD protocol under individual and collective attacks in the linear Gaussian channel. The results show that DMCS-BE-QKD can greatly enhance the ability to tolerate the channel loss and excess noise compared to the original DMCS-CVQKD protocol, which can tolerate approximately 40 dB more channel loss compared to the original DMCS-CVQKD for the realistic value of noise. Finally, a proof-of-principle experiment is conducted under a 50.5-km optical fiber to verify the feasibility of DMCS-BE-QKD. It is based on the consistent physical procedures of the traditional DMCS-CVQKD, which makes it perfectly compatible to deployed terminals and can serve as a multiplier for the practical secure quantum cryptography communication in harsh environments.